La cuestión del ser en Hans Urs von Balthasar : un estudio sobre Wahrheit der Welt - Llanes, Maximiliano (Sapientia, 2021)
In this article we propose to carry out a critical study on Wahrheit der Welt by H.U. von Balthasar in order to demonstrate in this work his reflection on the question of being. From this critical study emerge the ontological structures of being: the transcendentals, the "real distinction" between essence and esse / existence and the "polar tension" as a fundamental characteristic of the finitude of the real. His influences also emerge, and his criticism of Martin Heidegger’s understanding of "ontological difference". By means of his particular way of understanding the “real distinction” of Saint Thomas, Balthasar wants to differentiate himself from the different forms of modern Idealism and Transcendentalism, as philosophies of the identity between "God and the world" or between "thought and God."